2022
DOI: 10.3389/fcvm.2022.967115
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical multi-target strategies for myocardial ischemia-reperfusion injury

Abstract: Despite promising breakthroughs in diagnosing and treating acute coronary syndromes, cardiovascular disease’s high global mortality rate remains indisputable. Nearly half of these patients died of ischemic heart disease. Primary percutaneous coronary intervention (PCI) and coronary artery bypass grafting can rapidly restore interrupted blood flow and become the most effective method for salvaging viable myocardium. However, restoring blood flow could increase the risk of other complications and myocardial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 167 publications
0
15
0
Order By: Relevance
“…In addition, a variety of pharmacological approaches to cardioprotection, such as adenosine and glucose insulin potassium, have progressed to clinical testing for treatment of MI/R damage. Unfortunately, most clinical studies fail to provide evidence of the cardioprotective effects of conditioning strategies and pharmacological approaches [ 2 , 38 ]. There are several reasons why clinical translation fails, and here we present three major ones [ 39 ]: The pathophysiological mechanism of MI/R injury is complex, and understood only partially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a variety of pharmacological approaches to cardioprotection, such as adenosine and glucose insulin potassium, have progressed to clinical testing for treatment of MI/R damage. Unfortunately, most clinical studies fail to provide evidence of the cardioprotective effects of conditioning strategies and pharmacological approaches [ 2 , 38 ]. There are several reasons why clinical translation fails, and here we present three major ones [ 39 ]: The pathophysiological mechanism of MI/R injury is complex, and understood only partially.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a variety of pharmacological approaches to cardioprotection, such as adenosine and glucose insulin potassium, have progressed to clinical testing for treatment of MI/R damage. Unfortunately, most clinical studies fail to provide evidence of the cardioprotective effects of conditioning strategies and pharmacological approaches [2,38].…”
Section: Knowledge Basementioning
confidence: 99%
“…4 Effective clinical treatment to avoid reperfusion injury in patients is still elusive. 5 Therefore, it is important to research new strategies for mitigating reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…The reasonable combination of different protection strategies will help to activate complementary survival pathways and/or inhibit harmful cell death pathways, resulting in improved cardioprotective effects [15]. Animal experiments have recently confirmed that ischemic preconditioning protects against MIRI in diabetic rats by activating the serine/threonine protein kinase (Akt)-related signaling pathway and inhibiting apoptosis[13]. Therefore, multi-target therapy for MIRI is a novel approach for its treatment[15].…”
Section: Introductionmentioning
confidence: 99%